Automated volumetric assessment with artificial neural networks might enable a more accurate assessment of disease burden in patients with multiple sclerosis - Brugnara, Gianluca; Isensee, Fabian; Neuberger, Ulf; Bonekamp, David; Petersen, Jens; Diem, Ricarda; Wildemann, Brigitte; Heiland, Sabine; Wick, Wolfgang; Bendszus, Martin; Maier-Hein, Klaus H.; Vollmuth, Philipp (European radiology, 2020)
Patients with multiple sclerosis (MS) regularly undergo MRI for assessment of disease burden. However, interpretation may be time consuming and prone to intra- and interobserver variability. Here, we evaluate the potential of artificial neural networks (ANN) for automated volumetric assessment of MS disease burden and activity on MRI.
Gesehen am 14.04.2020